سياسة قرطاجة الافريقية 480-237 ق . م - عواد، وفاء, نعيمي، سعاد (جامعة الوادي university of Eloued, 2020)
الملخص:تأسست قرطاجة بشمال افريقيا على يد عليسةديدون بعد منحها قطعة أرض من طرف السكان المحليين الذين رحبوا بها حيث بنت مدينتها الجديدة واخذت هذه الاخيرة في التوسع في المنطقة وربطت علاقات مع جيرانها تميزت بالسلمية خاصة مع الليبيين اما مع روما فكانت عبارة على اتفاقيات ومعاهدات اما مع الاغريق فهي عبارة على منافسة تجارية في اطار سلمي الا ان هذه الاخيرة تحولت الى عدائية مع اشتداد التنافس الاقتصادي ما نتج عنه العديد من الحروب والمعارك اهمها معركة هيميرا سنة 480 ق.م والتي كبدت كلا الطرفين الكثير من الخسائر كل هذه بغية الاستيلاء على جزيرة صقلية وهذه المعركة أدت بقرطاجة الى التفكير نحو تغيير سياستها اتجاه الأفارقة والتوسع في غربي المتوسط حيث تحولت من البحر الى البر بالقيام برحالات استكشافية وشق الطرق التجارية وبناء المراكز والمستوطنات التجارية الجدية هناك وكان نتاج ذلك بازدهارها في عدة مجالات واهمها المجال الزراعي حيث استغلت الاراضي الليبية وسكانها في ذلك باللإضافة الى اكتشاف العديد من الموارد الجديدة واستحواذها على العديد من الاراضي واحتكارها لتجارة .كما كان لهذه السياسة انعكاسات على كلا الطرفين حيث توالت ردود الفعل الليبية على قرطاجة لاسترجاع اراضيهم واستغلال ابنائهم كمرتزقة في حروبها مع محاولة التحالف معهم في اوقات اخرى لكن دون جدوى وهذا ما أدى الى تفطن الرومان لها وخضوعها لهم اما بالنسبة لبلاد المغرب حيث لم تتمكن تمرداتهم من كسب أي شيء لأنها كانت عشوائية غير منظمة وانعدام ثقتهم في قرطاجة وخسارتها لأبنائها والعديد من اراضيها جراء سياسة قرطاجة الافريقية بالإضافة لإخضاعهم لضريبة اثقلت كاهلهم بها وهذا ما أدى الى شعورهم بالوعي الوطني مع ظهور الممالك الوطنية التى كان لها الدور البارز في ذلك وتحالفهم مع روما احيانا اخرى ضد قرطاجة مع توالي درد فعل الليبية الى ان وقفت قرطاجة وحيدة تكبلها الهزائم. Résumé qu: :فرنسية أو انجلزية Carthage was founded in North Africa by Alyssa Dedon after being granted a plot of land by the local people who welcomed her, as she built her new city and to expand in the region and tied relations with its neighbors that were characterized by peace, especially with the Libyans. But with Rome, it was an expression of agreements and treaties as for the Greeks It is a commercial competition in a peaceful context, but the last one turned into hostility with the intensification of economic competition, which resulted in many wars and battles, the important was the Battle of Himera in 480 BC, which inflicted on both parties a lot of losses, all of these in order to takeover the island of Sicily and this battle led Carthage to think about changing its policy towards the Africans and expanding in the western Mediterranean, where it turned from sea to land by undertaking exploratory trips, constructing trade routes and building new commercial centers and settlements there. The result of this was by its prosperity in several areas, the most important of which is the agricultural field, as it exploited the Libyan lands and its inhabitants in that in discovering Many new resources, its obsession of many lands and its monopoly on trade. This policy also had repercussions on both parties, as Libyan reactions continued to Carthage to regain their lands and to exploit their sons as mercenaries in its wars with the attempt to ally with them at other times, but with no availThis is what led the Romans to perceive it and its submission to them. As for the countries of the Maghreb, where their rebellions could not win anything because they were random and unorganized,and with their lack of confidence in Carthage and the loss of its people and many of its lands as a result of Carthage’s African policy in addition to their subjection to a tax that burdened them with it, and this what led them to feel with national awareness With the emergence of the national kingdoms that had a prominent role in that, and their alliance with Rome at other times against Carthage, with the succession of the Libyan reaction until Carthage stood alone, shackled by defeats .
مذكرة ماستر تاريخ تخصص تاريخ الحضارات القديمة
Keywords: قرطاج، معركة هيميرا; Carthage, bataille d'Himera; Carthage, Battle of Himera